Biomass production and photosynthetic efficiency of turmeric grown in different shade conditions - Ferreira, M. I. [UNESP]; Lima, G. P. P. [UNESP]; Rodrigues, L. F. O. S. [UNESP]; Silva, M. B. [UNESP]; Jadoski, C. [UNESP]; Goncalves, G. G. [UNESP]; Ming, L. C. [UNESP]; Patil, B.; Gafner, S.; Craker, L.; Mentreddy, SR (Int Soc Horticultural Science, 2016)
Biomass production directly or indirectly depends upon light. This experiment studied biomass production in turmeric (Curcuma longa L.) grown at anti-UV polyethylene, full sun, 30, 50, and 70% shade, in four harvests times. Our objective was to evaluate photosynthetic efficiency, leaf and rhizomes biomass production. The results show that plants grown under polyethylene showed higher photosynthetic efficiency parameters A, A/E and gs at 114, 169 and 201 DAP. These plants also had lower Tleaf over the period of cultivation. This was reflected in significantly higher production of rhizomes and leaf. We conclude that anti-UV polyethylene film provided better photosynthetic efficiency and biomass production for the growth of C. longa.
Keywords: Curcuma longa L., light levels; productivity; rhizome